Relationship Between Human Meibum Lipid Composition and the Severity of Meibomian Gland Dysfunction: A Spectroscopic Analysis - Nagar, Saumya; Ajouz, Layla; Nichols, Kelly K.; Kumar, Sandeep; Zhao, Cathy; Naidoo, Kugen K.; Robinson, Michael R.; Borchman, Douglas (Investigative ophthalmology & visual science, 2023)
Information on the relationship between meibum lipid composition and severity of meibomian gland dysfunction (MGD) is limited. The purpose of this study was to analyze the molecular components of meibum collected from individuals with no MGD, mild-to-moderate MGD, and severe MGD. Adults with and without MGD were enrolled in a prospective, multicenter, exploratory clinical trial (ClinicalTrials.gov Identifier: NCT01979887). Molar ratios of cholesteryl ester to wax ester (RCE/WE) and aldehyde to wax ester (Rald/WE) in meibum samples were measured with 1H-NMR spectroscopy. Results were evaluated for participants grouped by MGD disease status and severity (non-MGD, mild-to-moderate MGD, and severe MGD), as defined by maximum meibum quality scores, Schirmer test results, and Subject Ocular Symptom Questionnaire responses. Sixty-nine meibum samples from 69 individuals were included in the analysis: 24 non-MGD, 24 mild-to-moderate MGD, and 21 severe MGD. Mean RCE/WE was 0.29 in non-MGD, 0.14 in mild-to-moderate MGD (P = 0.038 vs. non-MGD, 51% lower), and 0.07 in severe MGD (P = 0.16 vs. mild-to-moderate MGD, 52% lower; P = 0.002 vs. non-MGD, 76% lower). Mean Rald/WE was 0.00022 in non-MGD, 0.00083 in mild-to-moderate MGD (P = 0.07 vs. non-MGD, 277% higher), and 0.0024 in severe MGD (P = 0.003 vs. mild-to-moderate MGD, 190% higher; P < 0.001 vs. non-MGD, 992% higher). RCE/WE was lowest and Rald/WE was highest in the severe MGD cohort, suggesting that these meibum constituent molar ratios may result from the pathophysiology associated with MGD and can impact ocular surface lipid and tear film homeostasis. These findings may potentially help identify targets for MGD treatment.